Pengembangan Materi Fikih Pada Materi Iddah Berbasis Website Di Pondok Pesantren - Sahla Mardhiah; Mardhiya Agustina (FKIP UNSULTRA, 2026)
Fiqh learning on the topic of iddah in Madrasah Aliyah still faces challenges due to limited integration with the concepts of talaq, rujuk, menstruation (haidh), and istihadhah, as well as the continued use of conventional learning methods. This study aimed to develop and evaluate the feasibility of a website-based learning medium that integrates these concepts into a comprehensive learning experience. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected through observations, interviews, documentation, expert validation, questionnaires, and learning assessments. The developed product comprised a teaching module and an interactive website designed to support students’ understanding of Islamic family jurisprudence. Validation results showed that the product achieved valid to highly valid categories, with expert assessments ranging from 71.43% to 90.48%. During implementation, students actively engaged with the learning activities and demonstrated positive responses toward the website. Questionnaire results indicated high levels of satisfaction regarding accessibility, clarity of content, attractiveness of the media, and support for independent learning. In addition, the integration of iddah with talaq, rujuk, haidh, and istihadhah helped students develop a more comprehensive understanding and stronger analytical skills in addressing Islamic legal issues. These findings indicate that the website-based learning media is feasible, effective, and capable of improving the quality of fiqh learning, particularly in the context of Islamic family law.